Questionnaires to assess chronic itch: a consensus paper of the special interest group of the international forum on the study of itch - Weisshaar, Elke; Gieler, Uwe; Kupfer, Jörg (Acta dermato-venereologica, 2012)
Chronic itch affects millions of patients worldwide and has a significant impact on quality of life....
Gesehen am 14.05.2019